Dietary 25-Hydroxycholecalciferol Supplementation from Day 85 of Gestation to Farrowing Enhances Performance, Antioxidant Capacity, and Immunoglobulins of Sows and Newborn Piglets - Shenfei Long; Shad Mahfuz; Xiangshu Piao (Animals)
In this study, the aim was to evaluate the effects of dietary 25-hydroxycholecalciferol supplementation from day 85 of gestation on performance, antioxidant capacity, and immunoglobulin level of sows and newborn piglets. On day 85 of gestation, forty Landrace × Yorkshire gestating sows (average body weight of 241 ± 6.8 kg; average parity of 3.47 ± 0.6) were allotted into two treatments (20 replicates per treatment) based on parity, body weight, and back fat thickness. From day 85 of gestation to farrowing, sows were fed a normal vitamin D3 diet as control (containing 50 μg/kg vitamin D3; CON), or a 25-hydroxycholecalciferol-supplemented diet (containing 50 μg/kg 25-hydroxycholecalciferol). Compared with CON, dietary 25-hydroxycholecalciferol supplementation increased (p < 0.05) protein and fat content in colostrum and the average birth body weight of newborn piglets. Sows fed 25-hydroxycholecalciferol showed increased (p < 0.05) apparent total tract digestibility of crude protein compared with CON. Diets supplemented with 25-hydroxycholecalciferol also increased (p < 0.05) the content of superoxide dismutase (SOD), and tended to increase (p = 0.06) the total antioxidant capacity content and reduce (p = 0.09) the malondialdehyde (MDA) level in colostrum. An increase (p < 0.05) in the content of SOD and a reduction (p < 0.05) in the content of MDA in the serum of newborn piglets was also observed in the 25-hydroxycholecalciferol treatment compared with CON. Dietary 25-hydroxycholecalciferol supplementation also enhanced (p < 0.05) the immunoglobulin G content and reduced (p < 0.05) the concentration of tumor nuclear factor-α in the serum of sows, as well as reducing (p < 0.05) the content of immunoglobulin G and immunoglobulin A in the serum of newborn piglets compared with CON. Supplementation of 25-hydroxycholecalciferol in sow diets increased (p < 0.05) the content of alkaline phosphatase in the serum and colostrum of sows, the concentration of insulin and crosslap in serum of sows, and the serum calcium content of newborn piglets compared with CON. In conclusion, dietary 25-hydroxycholecalciferol supplementation from day 85 of gestation could enhance performance, antioxidant capacity, and immunoglobulin in sows and newborn piglets.